The Gordian protocol - Weber, David, 1952-; Holo, Jacob (Baen, 2019)
"Doctor Benjamin Schroder was a history teacher until a psychotic episode turned his world upside down. Benjamin now had memories, not just of his own life, but of an entire ghastly world where millions of civilians had been systematically slaughtered in 'extermination camps,' there is still a Soviet Union, the Korean Peninsula is divided, thousands of nuclear warheads spread their threat across Earth and the Middle East was a festering sore of bloodshed, fanaticism and terrorism. Then a lunatic named Raibert Kaminski knocks on his door one afternoon with an impossible story of alternate realities, time travel, temporal knots and dozen of doomed universes that will die if the temporal storm front rushing towards the distant future isn't stopped. Of course he has to be lying--or completely insane. But what if he's not a madman after all? What if he's actually telling the truth?"--